Modeling and analysis of oil-palm biomass (opb) pyrolysis - Yahya Ayesh, Qasem Dahawi (2022)
Biomass-based pyrolysis is raising a growing interest nowadays because it can alleviate the pollution of biomass wastes and provide a supply of bio-energy, bio-fuels, and chemicals. Oil palm biomass wastes are Malaysia's most widely available and promising candidate feedstocks. The disposal of these wastes in a friendly environment is challenging. In this work, three types of oil palm biomass wastes - empty fruit bunch (EFB), palm kernel shell (PKS), and palm mesocarp fiber (PMF) - are examined to produce bio-char bio-oil and bio-syngas. The specific yields of these products depend on operating conditions of the pyrolysis processes, such as temperature, pressure, feedstock flowrate, and inert gas flowrate. These operating conditions can be optimized to maximize outputs. Bio-char has a variety of uses, such as in soil amendment, carbon storage, waste management, mitigation of climate change, energy source, and filter material. Bio-oil can be used as bio-fuel, energy sources, and chemicals. While bio-syngas can be used as a power resource, transportation bio-fuel can substitute natural gas. Specifically, the pyrolysis products are renewable for energy applications and economic and environmental benefits. The objectives of this study were to develop a steady-state model to simulate the pyrolysis of oil palm biomass wastes using ASPEN Plus V11, to predict and optimize the operating conditions on the production yields, and to optimize the economic potentials of the pyrolysis system. The pyrolysis system consists of a dryer, separator, primary and secondary pyrolyzers, solid-gas separator, two coolers, and liquid-gas separator. The pyrolyzer was modeled using the minimum Gibbs free energy method. Even though the simulation model is thermochemical equilibrium-based, it is valid, especially in determining the optimal operating conditions of the pyrolysis process. In addition, the Aspen plus optimization tool was used to optimize the economic potential of the system. The range of the operating conditions that have been applied in this study were 300 – 1000 °C, 1-10 bar, 10-100 kg/h of feed, and 10-100 kg/h of inert gas. Two scenarios applied in the economic optimization are the optimization model without bio-oil constrain and the optimization model with bio-oil ≥ 10 kg/h as a constraint and the feed flow rate was equal or less than 100 kg/h in the two scenarios. Simulation results showed that all the oil palm biomass wastes displayed a high syngas yield (51.02%), a moderate bio-char yield (29.9-34.4%), and a low bio-oil yield (14.6-16.1%) at standard pyrolysis conditions. The results perfectly agree with the reported literature (Visconti et al., 2015). The results show that the EFB is the best suited for syngas and bio-oil generation, whereas the PMF is appropriate for bio-char production. The optimum profit was obtained from EFB of approximately RM 357.8 per hour and RM 294.8 per hour in the first and second scenarios. It is hoped that the current simulation model outcomes can help to determine the optimal values of the operating conditions of the pyrolysis process and help to select feedstocks for bio-energy generation through the pyrolysis process. It has to be noted that the Aspen code could not predict the composition of the liquid residue.